A Study on Self-Confidence Impact of ELF Students’ Speaking - Novela Ananda; Hastini Hastini (Journal of General Education and Humanities, 2023)
Self-confidence plays a crucial part in speaking English, and many students are still less confident when speaking, which causes them to not engage more in speaking activities. This research aimed to know how self-confidence works in students speaking to ninth-grade students, specifically at SMP Negeri 9 Palu, and the factors that contributed to their lack of confidence. For the topic, 30 students were selected as the sample and given twelve questions from the questionnaire and five interview questions. The research method was a descriptive qualitative method. The results that the researcher has done are self - confidence indeed works on students’ speaking. Students’ lack of confidence is caused by some factors, which are afraid of making mistakes when they speak, they still have lack of vocabulary, lack of grammar, feel of under pressure every time the teacher asks them to speak, shyness, nervous, feel of uncomfortable, not enjoying when they attempt to speak, insecurities of their friends who have the good ability more than them. This study is expected to contribute to developing students’ speaking ability and solve students’ problems by knowing their speaking and what factors contribute to their unconfident. Moreover, this study also may help teachers treat students so they can participate actively in class without being constrained with self–confidence.